A New Chapter in the Human/Natural World Relationship? Geoengineering and Its Challenges to Environmental Governance - Jörgens, H. (II International Meeting: Histories of Nature and Environments - Shaping Landscapes, 2019)
Geoengineering technologies are a heterogeneous set of proposals for manipulating the global climate system which to date have not been put into practice on a large scale. Nevertheless, many experts and policymakers agree that the climate policy goals adopted in 2015 in the Paris Agreement cannot be reached without a strong reliance on these new technologies. From a policy perspective, the use of geoengineering technologies differs in important ways from the still dominant environmental policy paradigm. So far, technology-based environmental policymaking has mainly presented itself as making products, production processes and services less environmentally damaging and more eco-efficient, following an ecological modernization approach. In this framework, environmental regulation is seen to have a net positive effect that is directly visible to all actors (public and private organizations, civil society actors, voters etc.). The level of risk associated with the technologies of previous environmental policy instruments was generally considered to be lower than that associated with the problem they were designed to address. This is different with geoengineering. The potential risks and dangers of some geoengineering technologies such as carbon capture and storage or solar radiation management are often considered to be much greater than those of previous environmental regulatory approaches (with the exception of nuclear energy). At the same time, many of the technologies that figure under the label of geoengineering – unlike other types of environmental policy instruments – actually contradict common perceptions of a “greening” of the economy and of society. For example, Bioenergy With Carbon Capture and Storage (BECCS) implies a strong reliance on genetically modified crops. Carbon storage is a potential threat to the oceans and other eco-systems. The reliance on large-scale technological responses in general runs counter to dominant values and ideologies of the environmental movement that are based on ideas of decentralization (for example in the field of renewable energy), regionalization (for example in the field of sustainable consumption) and a general assumption that the world has to move into an era of degrowth. This lack of compatibility of geoengineering with the values and belief systems of the environmental protection movement is problematic insofar as this movement constitutes, in principle, one of the key actors in the ongoing transition to a more sustainable world. The keynote discusses some of the governance problems that may arise from a greater reliance on geoengineering technologies in the near future.